SOCIO-CULTURAL MISMATCH STUDY ON THE EXISTENCE OF JEPARA 1001 BOARDING SCHOOL - Kurniawan, Muhammad Andi; Ramadhani, Regita Septia; Thalita, Nabila Rizqia (Jurnal Penelitian Humaniora, 2023)
This research is motivated by the existence of Jepara as the City of 1001 Islamic Boarding Schools, the dilemma in the Stereotype Mismatch Study is the socio-cultural portrait of the community that does not reflect the inherent social identity and labels. This is shown by the high social and juvenile delinquency cases such as free sex, narcotics, racing liars and the degradation of morality and character of the younger generation. Therefore, through scientific studies with a socio-cultural approach, it forms the basis of a framework for viewing ethnography that occurs in society, with the case study of Bangsri Village, Jepara Regency. This study used a Qualitative Method with an Ethnographic research design to analyze, view, and explain the condition of the people studied through descriptive studies. The research base is located in Bangsri Village, Jepara Regency. Data collection was obtained through primary and secondary data sources, with data validity techniques through source and technique triangulation and using interactive data analysis models. The results of this study are expected to provide alternative guidelines and references in maximizing Jepara's Existence as a City of 1001 Islamic Boarding Schools with the basis of Civil Society which upholds the values of the Islamic Religion and the progressive Al-Qur'an.